Heartsick: psychiatric and inflammatory implications of cerebromicrovascular disease. (6th November 2013) - Nemeth, Christina L.; Haroon, Ebrahim; Neigh, Gretchen N.
<x xml:space="preserve">Abstract</x> Background Cerebromicrovascular disease (CMVD) strikes 87% of the population older than 65 years and is linked to an increased risk of ischemic stroke, depression, cognitive impairment, and Alzheimer's disease. Despite the wealth of knowledge on the consequences to the body stemming from poor vascular health, little focus has been placed on the consequences to the brain. Design In this review, we present the preclinical and clinical evidence that supports the role of CMVD in behavioral dysfunction, argues for a clinical need for better recognition of the vascular depression phenotype, and calls for a more integrative translational approach to CMVD. Results and conclusions Although the concept of cerebrovascular‐induced behavioral change has existed for over 100 years, the difficulty of diagnosis, the slow progression of CMVD, and the lack of causative data have led to an underestimation of the patient population and poor treatment strategies. Preclinical studies have focused on the use of microsphere embolic models and vascular inflammation models to assess the mechanisms of, and treatment options for, CMVD. Though preclinical models provide support for correlative data collected in the clinic, translational reciprocity has not been established. The lack of clinical appreciation for the role of cerebrovascular health in brain function may result in missed diagnoses and inadequate treatment of underlying cardiovascular disease. Enhanced recognition of symptoms and disease presentation will allow for earlier prevention, detection, and identification of novel targets for drug development and other intervention strategies. Copyright © 2013 John Wiley & Sons, Ltd.